Relationship between workload and organizational citizenship behavior in community nursing service management in Indonesia - Miftahul Munir; Karyo Karyo; Umu Qonitun (Healthcare in Low-resource Settings)
The management of community nurse services is essential for enhancing public health. Factors such as workload, organizational support, and job satisfaction influence organizational citizenship behavior (OCB), which impacts the quality of nursing governance. This research investigated the relationship among workload, OCB, and community nurse management using a quantitative correlational approach with 171 community nurses from health service centers in Tuban Regency, Indonesia. Simple random sampling was used to ensure equal representation of the participants. Data were collected using structured questionnaires that measured workload, OCB, and nurse governance. Spearman’s correlation test was used to analyze the relationships between these variables. The findings indicated that 46.7% of respondents exhibited high OCB, while 45.8% rated community nurse governance as good. Regarding workload, 50% of respondents reported a moderate workload. Statistical analysis revealed a significant correlation among workload, OCB, and nurse governance (p<0.05). Higher OCB levels were associated with better governance, while a moderate workload contributed to more effective nurse management. Balancing workloads and fostering OCB is crucial to enhancing nursing governance and healthcare service quality. Strengthening organizational support, implementing targeted training programs, and improving nurse management strategies can contribute to more effective community health services. Future research should consider psychosocial stress and emotional burden when developing a comprehensive workload assessment model.